Irony of a revolution: how grassroots organizations reinforced power structures they fought to resist - Lynn, Tamara J. (Kansas State University, 2014)
This study is about two grassroots political organizations that formed prior to the 2012 presidential election in the United States, each concerned with the nation's economy, corporate favoritism, government involvement, and growing income inequality. The study outlines an historical account of a culture of control, and then analyzes actions of two contemporary protest organizations – The Tea Party, known as politically conservative; and Occupy Wall Street (OWS), characterized as liberal – as the national election unfolded. Each group sought to change the political landscape and influence the outcome of the presidential election, but with competing messages and very different approaches. Seeking change from the inside, The Tea Party emphasized limited government regulation of the market economy. OWS intended to crumble the system by outside resistance and demanded government attention to economic inequality. Field research and content analysis provide insight into behaviors, beliefs, and actions of each group, which, in turn, identify efforts to resist the status quo. Content analysis of print news provides evidence of state responses toward each group, while also offering insight into media framing and public influence. Finally, a survey of official responses from host communities reveals specific efforts to control protest organizations, ranging from acts of diplomacy to violent opposition. Findings demonstrate how roles of the Tea Party and OWS are not always in conflict, such as media often portray; for example, both groups contested corporate control. The Tea Party met token success, but stopped short of influencing top echelons. OWS brought attention to system inequities, but failed to maintain significant pressure; instead, participants were criminalized for acts of protest. Ironically, in the end, both groups' efforts reinforced the culture of control they sought to resist. Theoretically, a cultural criminology framework, integrating symbolic interaction and social control, demonstrates how structural constraints oppose grassroots political efforts.
Keywords: Cultural criminology; Grassroots Political Organizations; Tea Party; Occupy Wall Street; Social control; Ideology; Criminology (0627); Sociology (0626)